Simultaneous enhancements of mechanical properties and hydrophilic properties of polypropylene via nano‐silicon dioxide modified by polydopamine. Issue 26 (6th March 2017) - Qiu, Zhoutong; Wang, Jikui; Yang, Kun; Guo, Jiahong; Wang, Wenqi; Pan, Renjie; Wu, Genhua
ABSTRACT: This study is focused on the development of high‐performance composite materials based on nano silicon dioxide (nano‐SiO2 ) modified by polydopamine (PDA). A facile one‐step method was developed to synthesize core–shell structured SiO2 @polydopamine (PDA) nanospheres. During the synthesis, a PDA shell was simultaneously coated on the SiO2 nanospheres to form the core–shell nanostructure which was blended with polypropylene (PP) and β nucleating agent (β‐NA) to enhance both mechanical and hydrophilic properties. Nano‐SiO2 particles modified by PDA (SiO2 @polydopamine) influence the crystallization of PP seriously. The results indicated that when 1%wt SiO2 @polydopamine was added, the impact strength of composite reached the maximum value 12.60k J/m 2 increasing 137% compared with PP, the bending strength and bending modulus decreased slightly reaching 41.85 MPa, and 2192 MPa, respectively, the composite possessed hydrophilic performance with the water contact angle of 88.32°. β nucleating agent was used in all formulations, the synergistic effect toward mechanical properties with SiO2 @polydopamine was studied. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45004. Abstract :